1995
DOI: 10.1007/bf01839331
|View full text |Cite
|
Sign up to set email alerts
|

The equine enteric nervous system — Neuron characterization and distribution in adults and juveniles

Abstract: A study of myenteric and submucosal plexuses was undertaken in the jejunum and ileum of horses and ponies in which no clinical or pathological evidence of intestinal abnormality was apparent. Complete transverse sections of the intestine, stained by a modified haematoxylin and eosin method, were examined using up to 20 sequential sections per animal. Information was gathered from adult, juvenile and fetal equidae. In adults, the longitudinal muscle layers were thinner than the circular muscle layers and the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
11
1
1
Order By: Relevance
“…Gabella (1971) observed in developing rats that the neuronal density decreased with age. Similar observations have been made in guinea-pigs, sheep, horses, pigs, and chick embryos (Gabella, 1987;Young et al, 1993;Doxey et al, 1995;Zhang et al, 2004;O′Donnell et al, 2006). Decreasing NADPH-dpositive neuron density in the developing pig model has been used to explain why primary intussusception does not occur in adults (Cserni et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…Gabella (1971) observed in developing rats that the neuronal density decreased with age. Similar observations have been made in guinea-pigs, sheep, horses, pigs, and chick embryos (Gabella, 1987;Young et al, 1993;Doxey et al, 1995;Zhang et al, 2004;O′Donnell et al, 2006). Decreasing NADPH-dpositive neuron density in the developing pig model has been used to explain why primary intussusception does not occur in adults (Cserni et al, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…Neuronal loss in the myenteric plexus, as well as neuromuscular dysfunction, has been demonstrated to occur with human ageing (Hall, 2002;Hanani et al, 2004). In a study involving horses up to 20 years of age, Doxey et al (1995) found no decline in the number of small intestinal enteric neurons with increasing age. Additionally, Schusser and White (1997) found no significant difference in colonic neuronal density in normal horses that were 8 years old or less compared with animals over 8 years old.…”
Section: Discussionmentioning
confidence: 98%
“…The problem with previous research -in healthy horses -has been the use of 2-D quantitative microscopy methods (membrane preparations) for assessing enteric neurons [Pearson, 1994;Doxey et al, 1995;Freytag et al, 2008]. After perusing the literature, surprisingly, we have not yet found any 3-D design-based stereological data on the enteric nervous system of healthy and ICA horses.…”
Section: Introductionmentioning
confidence: 81%
“…Another study conducted on the ileum of healthy horses by Doxey et al [1995] estimated the number of neuron profiles in the myenteric and submucosal plexuses of horses as 8,808 and 14,352, respectively. Again, our estimates for the horse ileum were 5,264-and 1,144-fold higher, respectively.…”
Section: Discussionmentioning
confidence: 99%